SOSIALISASI APLIKASI MOBILE PARAK ACIL (PELAYANAN PENDAFTARAN PENDUDUK DAN PENCATATAN SIPIL) ONLINE DI KOTA BANJARMASIN - Erma Ariyani; Rahmatun Nisa; Susi Hardjati (Jurnal PubBis, 2024)
The Banjarmasin City Government has innovated its services by creating the "Banjarmasin Pintar" application, which is part of Banjarmasin's smart city programme. The mobile application PARAK ACIL (Population Registration and Civil Registration Services) Online is a public service application designed for residents to access services, particularly those provided by the Population and Civil Registration Office of Banjarmasin City. This study aims to examine the socialisation efforts conducted by the Population and Civil Registration Office of Banjarmasin City regarding the PARAK ACIL mobile application. The research employs a descriptive qualitative method. Data collection techniques include observation, interviews with 6 informants, and documentation. The data was analysed using Cresswell's method, which involves organising and preparing the data, reviewing the overall data, creating codes, and using those codes to develop descriptions, then connecting and interpreting the data. The results of the study indicate that the socialisation process of the PARAK ACIL Online mobile application in Banjarmasin City has been fairly optimal. However, there are still residents who prefer to visit the Population and Civil Registration Office in person, indicating the need for enhanced and modernised socialisation techniques that align with current trends. Keywords: Socialisation, Smart City, PARAK ACIL Online